O-276 Reproductive outcomes and fertility-sparing in women with Borderline ovarian tumors. (30th June 2022) - Uzan, C; Canlorbe, G; Chabbert-buffet, N
Abstract: The standard treatment of BOT is defined as a total abdominal hysterectomy and bilateral salpingo-oophorectomy, peritoneal cytology, omentectomy and multiple peritoneal biopsies. These procedures allowed to perform an adequate staging, most of the time no adjuvant treatment is necessary except in case of associated invasive peritoneal implants. The prognosis of BOT is excellent. However, late recurrences (after 5 or 10 years) can be observed. Conservative surgery is defined as preservation of the uterus and at least part of one ovary, in order to preserve fertility. BOT arise in a young population, for whom fertility is a major issue. The global recurrence risk is estimated at 13%. The rate of recurrence is correlated with the type of conservative treatment used (salpingo-oophorectomy or cystectomy) with a higher rate of between 10 and 42% in patients undergoing cystectomy. In the case of bilateral serous BOT, if technically feasible, bilateral cystectomy should be performed to improve pregnancy rates. For serous BOT e cystectomy can be performed (tumour can be bilateral for 20% of these patients) with a close follow up by ultrasound. For mucinous BOT, salpingo-oophorectomy is recommended to avoid rare but at risk invasive recurrence, (these lesions are usually unilateral). A complete evaluation must be performed preoperatively including MRI with evaluation of possible safe functional ovarian tissue and oncofertility consultation to discuss if fertility preservation technique can be proposed before surgery. The observed pregnancy rates observed after conservative surgery are between 32 and 88%. Different factors can influence fertility rates: type of conservative treatment, age of the patient (with almost a quarter of the live birth occurring after recurrence with no more further event to date, a second fertility-sparing surgery after local borderline recurrence can be proposed in the case of pregnancy project), histologic subtype of the tumour (better with mucinous versus serous), the use of a laparoscopic approach and the use of a 2- or 3-step surgery (initial, restaging, second look). In spite of conservative management in BOT, some patients will experience infertility. In vitro fertilization (IVF) procedures have not been significantly associated with a specific increase in BOT or ovarian cancer rates.  In vitro data suggest that gonadotropins and/or high dose of estrogens don't induce a borderline cell cultures proliferation. Analyzing all series reporting IVF and BOT, the pooled estimate for pregnancy was 80% (95% CI: 68–92%). The pooled estimate for recurrence was 23% (95% CI: 6–39%). The rate of recurrence in these women is 'low' though this is probably due to the fact that women who are selected as eligible for ART have a better prognosis and more often early-stage BOT. However, there is a real need for fertility preservation expert centers associating oncologists and fertility experts who can evaluate conservative management of BOT along with alternative therapeutic options to preserve fertility as well as ART.